2020
DOI: 10.1007/s00381-020-04921-y
|View full text |Cite
|
Sign up to set email alerts
|

Posterior ischemic optic neuropathy following supine craniotomy for epidural abscess in a child

Abstract: Post-operative vision loss (POVL) can be a devastating complication of neurosurgical procedures and is unusual in the pediatric population. Mechanisms of POVL include direct optic nerve injury, vascular occlusion, or indirect malperfusion resultant from surgeries with substantial blood loss or fluid shifts, with prone positioning being a major risk factor for these events. Posterior ischemic optic neuropathy (PION) is a rare cause of POVL and is associated with a poor prognosis for recovery of visual function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is associated with multifactorial systemic diseases such as diabetes mellitus, hypertension, atherosclerosis or other causes (carotid artery dissection, carotid cavernous fistula) (9), migraine (8,10,11), associated with haemodialysis (8,12), or head injury (8). Perioperative conditions can also be the cause (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with multifactorial systemic diseases such as diabetes mellitus, hypertension, atherosclerosis or other causes (carotid artery dissection, carotid cavernous fistula) (9), migraine (8,10,11), associated with haemodialysis (8,12), or head injury (8). Perioperative conditions can also be the cause (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al, in 2021, reviewed ophthalmic complications associated with perioperative anesthesia, citing literature indicating that spinal fusion surgeries are associated with both ION and CRAO [60]. Oliver et al, in 2021, reported a 9-year-old boy who was diagnosed with posterior ION following supine craniotomy for an epidural abscess [61]. Mulukutla, Yelemarthy, and Vadpalli, in 2021, presented a 46-year-old female who underwent anterior cervical discectomy and fusion and developed bilateral loss of vision 9 h after the surgery, and was found to have cortical blindness [62].…”
Section: -Presentmentioning
confidence: 99%
“…The presentation of PION will be consistent with optic neuropathy, but with an unremarkable fundoscopic exam [36]. While PION is often a diagnosis of exclusion, recent reports have argued for the use of diffusion weighted imaging (DWI) to diagnose the acute phase of PION [55,61,65]. DWI has been applied to AION and shows promise in detecting ischemic changes [81].…”
Section: Assessment and Diagnosismentioning
confidence: 99%